Tooth Number Design of Multi-stage Parallel Shaft Gear Reducer based on Accurate Transmission Ratio - Lixuan Zhou; Hexiang Yuan; shoubang Zheng; Dengfeng Luo; Yongqin Qiao (Jixie chuandong)
With the design objective of accurately ensuring the total transmission ratio of the multi-stage parallel shaft gear reducer， the mathematical relations among the gear parameters are studied under the conditions of given center distance and total transmission ratio. The mathematical model of gear tooth number selection of multi-stage reducer is established. The program for calculating the number of teeth of the multi-stage gear reducer is developed， which enables the designer to quickly determine the number of teeth of each gear of the multi-stage parallel shaft gear reducer， and ensure the center distance of each stage and the total transmission ratio accurately within the reasonable value range of modulus， helix angle and modification coefficient.